Following the legacy of professors Barbara Starfield and Leiyu Shi in Brazil as health policy: the National Health Survey (PNS), led by the Brazilian National Institute of Geography and Statistics (IBGE) and the Primary Care Assessment Tool (PCAT) - Erno Harzheim; Luiz Felipe Pinto; Otavio Pereira D'Avila; Lisiane Hauser (BMC, 2019)
Abstract We present to the scientific community the pioneering of Brazilian National Institute of Geography and Statistics (IBGE, the Brazilian Census Bureau) in partnership with the Ministry of Health, the largest fieldwork ever conducted in a single country in the world, using the PCAT in a national household sample survey, visiting more than 100,000 households and 40% of the country's municipalities. In Brazil, PCAT is being consolidated as an instrument to support public policy for the evaluation of primary health care. We believe that it represents a virtuous example of dialogue between scientific community and health management, following the legacy of Professors Barbara Starfield and Leiyu Shi.